Regional differences and threshold effect of clean technology innovation on industrial green total factor productivity - Sun, Haibo; Zhang, Zan; Liu, Zhonglu (Frontiers in Environmental Science, 2022)
Guiding technological progress towards clean innovations is crucial to industrial green transformation. This paper explains how clean technology innovation affects industrial green total factor productivity, using Tobit and panel smooth transition regression (PSTR) models to empirically test the relationship between clean technology innovation and industrial green total factor productivity. This research shows that clean technology innovation has a significantly positive effect on industrial green total factor productivity. The magnitude of this effect is different in various regions. When the intensity of environmental regulation reaches a particular threshold value in the central and western regions, clean technology innovation can significantly promote industrial green total factor productivity. In the eastern region, however, strict environmental regulation inhibits the promotion effect of clean technology innovation on industrial green total factor productivity. The corresponding research conclusions provide theoretical support and empirical evidence for exploring the way of industrial green transformation.